FYP examiner allocation system improvement - Ho, Audrey Hai Yi (2019)
Final Year Project (FYP) is part of most student’s curriculum, and in the School of Computer Science and Engineering, Nanyang Technological University, it is compulsory. Supervisors will oversee the projects for over one year. Hereafter, the final product is assessed and graded by both the supervisor and the examiner. The process of allocating examiners to the project is one of the features of the FYP Examiner Allocation (FEA) System. The FEA system had commenced in 2007 when a group of final year students aimed to resolve the challenges faced by the FEA coordinator. Manually assigning duties to faculty staffs and planning of the presenting schedule are few of the hurdles met. Through the years, improvements were a necessity when the number of issues was growing. After examining the system and discussing with the team, change request and new features were brought up. Better performance, security, and scalability were part of the enhancements mentioned, allowing the users to have a better user experience.